Digital competences in the social media program for older adults in vulnerable contexts - Holguin Alvarez, Jhon Alexander (2020)
In this study we analyze the effects of the program of incursion in Social Networks in Digital Competences as part of an experimental investigation with 40 adults (rank: 81 - 92 years of age) from vulnerable contexts of a Latin state. 50 educational activities based on the use of Facebook, WhatsApp, Twitter and Gmail were applied as essential elements of virtual communication. These allowed obtaining statistical significance in digital competencies of the experimental group, especially in more than 60% of participating subjects, both in the ability to manage technological resources as well as in the interrelation through the internet (social networks). The study recognizes its contribution in the opportunity to generate digital inclusion in the elderly in states of digital abandonment.